Implementasi Kurikulum Merdeka Belajar Pada Mata Pelajaran Geografi di SMA Se-Kota Palu - Yulianti; Nurvita (Jurpis: Jurnal Pendidikan Ilmu Sosial, 2024)
This research is a qualitative study which aims to determine the implementation of the independent learning curriculum at 3 driving schools in the city of Palu, consisting of schools: SMA Negeri 7 Palu, SMA Negeri 4 Palu and SMA Negeri Sports Tadulako Palu. The subjects in this research were 3 geography subject teachers at 3 Driving Schools in Palu City. The results of this research show that: 1) At the SMA Negeri 7 Palu school, at the implementation stage, the flow of learning objectives is not yet fully based on the needs of students, the teaching tools still combine the independent curriculum and the 2013 curriculum, collaboration has not been implemented between teachers and parents, guardians/students, obstacles What is experienced in the implementation of the independent learning curriculum is inadequate infrastructure: infocus, internet networks and the implementation of the independent learning curriculum is not evenly distributed at all levels of school which makes it difficult for students to adapt; 2) At SMA Negeri 4 Palu there has been no collaboration with parents, guardians/students and the industrial community; 3) At Tadulako Palu Sports Public High School, collaboration with parents, guardians/students and the industrial community has not yet been carried out. The obstacles to implementation are that learning resources in the independent learning curriculum are reduced and training to master the independent learning curriculum is inadequate.